PREVALENCE AND FORMS OF ONLINE HARASSMENT AMONG UNDERGRADUATES OF A NIGERIAN UNIVERSITY - Mulikat Ladi Mustapha; Shuaib Abolakale Muhammad; Faith Folusho Olowoniyi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
The upsurge in accessing and utilizing the internet and social networking sites for social activities predisposes adolescents and young adults globally to online harassment, Nigerian undergraduates inclusive. The impacts of online harassment have attracted many research interests, especially in the developed world and the dearth of inquiries among Nigerian undergraduates. This work inquired about the prevalence and forms of online harassment perpetrated by undergraduates in a Nigerian university. A descriptive research design was adopted, data were amassed utilizing a three-sectioned self-report form administered on a sample of 420 undergraduates. The selection of the sample was made following a multistage procedure. Percentage and univariate analysis techniques were used for data analysis. The result of the inquiry revealed widespread online harassment among the undergraduates of the university. All the forms of online harassment assessed were perpetrated; dog pilling topped the list (63.1%), followed by trolling (44.0%). The high rate of occurrence demands the urgent attention of the university authority, professionals across relevant fields should create awareness; the need to develop interventions and policies to deal with online harassment is obvious